Synthesis and antituberculosis activity of the first macrocyclic glycoterpenoids comprising glucosamine and diterpenoid isosteviol. (5th August 2016) - Garifullin, Bulat F.; Strobykina, Irina Yu.; Sharipova, Radmila R.; Kravchenko, Marionella A.; Andreeva, Olga V.; Bazanova, Olga B.; Kataev, Vladimir E.
Abstract: The first macrocyclic glycoterpenoids comprising glucosamine and diterpenoid isosteviol moieties were synthesized and evaluated for inhibition activity against Mycobacterium tuberculosis H37Rv. Graphical abstract: